A demokrácia értelmezése a posztkommunista országokban - Simon, János (Szociológiai Szemle, 2024)
By processing the answers to open questions we analyzed with content analysis what the concept of democracy means for Hungarians. We analised the citizens interpretations of democracy during the transition to democracy based on the example of the Hungarians trough a time-series surveis (in 1989. 1990 and 1993). We joined the meanings of democracy in the following 7+1 categories groups: freedom, participation, social well-being, elections, right, values, emotions, tempers and other. Then we compared the Hungarian results with the picture of democracy of the citizens of an East European (Romania) and a West European country (Spain). According to our opinion the considerable difference can be explained by the differing character of the old authoritarian regimes.